2018
DOI: 10.11609/jott.3487.10.6.11710-11716
|View full text |Cite
|
Sign up to set email alerts
|

<b>People’s attitude towards wild elephants, forest conservation and Human-Elephant conflict in Nilambur, southern Western Ghats of Kerala, India</b>

Abstract: Conflict with elephants and subsequent economic losses negatively affect residents’ tolerance towards wild elephants.  It is important to understand people’s attitude towards wildlife, especially Asian Elephants with an endangered status.  A questionnaire survey was undertaken with 510 forest fringe residents of Nilambur North and South Forest Divisions, Kerala, to understand residents’ attitudes towards elephant conservation and Human-Elephant conflict.  The majority of the villagers experienced psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
8
1
Order By: Relevance
“…While this relationship existed, however it is important for management to engage in active mobilization of outreach initiatives to educate communities about regulations and importance of the park's existence. Similar sentiments have been echoed elsewhere in Nepal [77], India [85], and South Africa [2,55,58].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…While this relationship existed, however it is important for management to engage in active mobilization of outreach initiatives to educate communities about regulations and importance of the park's existence. Similar sentiments have been echoed elsewhere in Nepal [77], India [85], and South Africa [2,55,58].…”
Section: Discussionsupporting
confidence: 78%
“…Perhaps communities that were further away were less likely to see or appreciate the benefits of KTP, and hence lacked support. This finding contrasted with other studies as communities that were in close proximity to PAs were found to have negative attitudes due to human-wildlife conflicts along with crop and livestock depredation [78,85,86]. For example, in Uganda, farmers who lived closer to and had farms on the boundary of Kibale National Park expressed negative attitudes toward the park and staff [4].…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations